Population Pharmacokinetics and Pharmacodynamic Target Attainment of Vancomycin in Neonates on Extracorporeal Life Support. Issue 10 (October 2017) - Cies, Jeffrey J.; Moore, Wayne S.; Nichols, Kristen; Knoderer, Chad A.; Carella, Dominick M.; Chopra, Arun
Abstract : Objectives: To evaluate the population pharmacokinetics and pharmacodynamic target attainment of vancomycin in neonates with a contemporary ¼-inch extracorporeal life support circuit with a Quadrox-iD Pediatric oxygenator (Maquet Cardiovascular, LLC, Wayne, NJ). Design: Retrospective medical record review. Setting: Two free-standing tertiary/quaternary pediatric children's hospitals. Patients: Neonates receiving either veno-arterial or veno-venous extracorporeal life support and vancomycin for empiric or definitive therapy with resulting serum concentrations. Interventions: None. Measurements and Main Results: Twelve patients with a median gestations age of 39 weeks (range 36–41 wk) and a median postnatal age of 9.5 days (range 0–28 d) accounted for 14 courses of vancomycin therapy while on extracorporeal life support and were included in the analysis. The median weight was 3.1 kg (range 2.2–4.41 kg) with five of 12 patients (41.7%) being female. Vancomycin concentrations were best described by an one-compartment model incorporating allometric scaling of estimated glomerular filtration rate on clearance. The mean total body clearance (mL/min/kg) for the population was 3.48 ± 1.31 mL/min/kg, and the mean total volume of distribution (L/kg) for the population was 1.2 ± 0.4 L/kg. The intermittent and continuous infusion dosing regimens that provided for the highest percentage of trough concentrations in the range of 10–20 mg/L were the 10 mg/kg/dose IV q8h, 12.5 mg/kg/dose IV q8–12h, 15 mg/kg/dose IV q12h, and 20 mg/kg/dose IV q12h, and the 20, 25, and 30 mg/kg/d continuous infusion regimens, respectively. All regimens allowed for an area under the concentration:minimum inhibitory concentration ratio of 400:1 for minimum inhibitory concentrations of less than or equal to 0.5 mg/L for a 90% PTA. None of the simulated regimens had a greater than 90% probability of achieving an area under the concentration:minimum inhibitory concentration ratio of 400:1 for vancomycin minimum inhibitory concentrations greater than or equal to 1 mg/L while maintaining trough concentrations in the range of 10–20 mg/L. Conclusions: To our knowledge, this is the first pharmacokinetic and pharmacodynamic study of neonates receiving vancomycin with a contemporary ¼-inch extracorporeal life support circuit including the Quadrox-iD Pediatric oxygenator (Maquet Cardiovascular, LLC). The data suggest differences in vancomycin pharmacokinetics compared with previous extracorporeal life support data, notably a more rapid clearance, which could result in lower vancomycin concentrations. Considering this, a more aggressive initial dosing regimen may need to be employed in infants on extracorporeal life support.